ANALISIS PERBANDINGAN KINERJA PERUSAHAAN DOMESTIK DAN ASING DENGAN MENGGUNAKAN ANALISIS RASIO MODAL SAHAM - Syahrul Syarifudin; Teti Rahmawati (Program Studi Akuntansi, Universitas Kuningan, 2019)
There are companies that stand in Indonesia that are owned by foreigners. People tend to judge that the performance of foreign companies is better than domestic companies. This is due to the assumption that foreign companies have relatively larger capital, technology, and expertise that is better than domestic companies. Another presumption is that before, during, and after the crisis the performance of foreign-owned companies is better than domestic companies. In addition, to find out the good and bad performance of a company, it can use a stock capital ratio analysis. With this stock capital ratio, it can be seen the rate of return on equity, the ratio of earning per share, profit price, capitalization rate, and dividend income. So that the analysis can help investors and potential investors as sources of information support in investing in the company. The results of the data analysis using the T-test (Difference Test) found that there was no significant difference between the return on equity ratio, earnings per share ratio, the profit price ratio, the capitalization rate and dividend income. Thus the performance of domestic companies is significantly similar to the performance of foreign companies.Keywords: Earning per share, profit ratio, , capitalization ratio